The Internal Aspects of Change on Language Used by Digital Native in Facebook Status Update - Ramli Hasan Aif; Soeparto Soeparto (University of Muhammadiyah Malang, 2014)
The Internal Aspects of Change on Language Used by Digital Native in Facebook Status Update